No Long‐Term Effect Two Years after Intrauterine Exposure to Dexamethasone on Dentate Gyrus Volume, Neuronal Proliferation and Differentiation in Common Marmoset Monkeys - Tauber, Simone C. (Brain Pathol, 2008)
Glucocorticoids are prenatally administered to promote the maturation of the lungs. They, however, can affect neuronal proliferation and differentiation. In newborn marmoset monkeys, intrauterine hyperexposure to dexamethasone (DEX) resulted in a significantly decreased proliferation rate in the hippocampal dentate gyrus without affecting neuronal differentiation. In this study, marmoset monkeys received 5 mg/kg body weight DEX either during early (days 42–48) or late (days 90–96) pregnancy. The volume of the dentate granule cell layer as well as the proliferation and neuronal differentiation in the dentate gyrus of their 2‐year‐old offspring were investigated. The density of proliferating cells (Ki‐67), apoptotic cells (in situ tailing) and cells differentiating to neurons (double cortin, TUC‐4 and calretinin) were determined immunohistochemically. Analysis of the dentate granule cell layer volume showed no significant differences between early or late DEX‐exposed marmosets and untreated control animals. Similarly, proliferation and neuronal differentiation in DEX‐treated animals was not significantly different in comparison with controls. In summary, the decreased proliferation rate observed in newborn marmosets after intrauterine exposure to DEX was no longer detectable in their 2‐year‐old siblings suggesting no long‐lasting effect of prenatal hyperexposure to DEX on neuronal proliferation and differentiation in the dentate gyrus of marmoset monkeys.